Psicosi epilettiche croniche e sindromi pseudoschizofreniche - Fagioli, Massimo (Il sogno della farfalla, 2010)
In this article dated 1962, originally published in “Annali di freniatria e scienze affini”, the Author examines five cases of chronic psychoses which appeared in epileptic patients. He points out their characteristics which appear different from other types of psychoses particularly from schizophrenia. The personality of patients does not change, the patients are not autistic, their deliriums present concrete, realistic elements and an adherence with their surroundings which distinguish them from schizophrenic deliriums.